O racismo na política de drogas e a defesa social na política judiciária: uma análise do discurso das decisões de habeas corpus no Tribunal de Justiça de Goiás - Santos, Ícaro Melo dos (2024)
The research investigates the intersection between racism in drug policy and societal defense, using the jurisprudence of the State Court of Goiás as an empirical basis for analysis, within the challenging context of the Covid-19 pandemic. Employing approaches from Critical Discourse Analysis (CDA) and Critical Criminology, the research relies on fundamental concepts such as discourse, power, ideology, and hegemony to identify discursive aspects that perpetuate racism in criminal sciences and influence judicial decisions. Throughout the investigation, discourses of the societal defense ideology persisting in the legal system were identified, utilizing legal institutions such as personal search, inviolability of the domicile, and the agent's dangerousness. These practices are intrinsically linked to an ideology promoting hegemony, necessitating constant critique of the undeclared functions of the penal system. As a result, recommendations were suggested to mitigate and modify identified discursive practices. It is proposed to establish a Permanent Observatory for Analysis of Judicial Decisions to monitor and evaluate the legislation's application based on anti-racism principles, as well as to amend requirements in the professional development of court officials and in leadership and advisory positions within the State Court of Goiás (TJ/GO). Furthermore, altering the objective promotion criteria in the judiciary career is suggested as a means to promote an equitable approach in the judicial system. These recommendations aim not only at identifying and critiquing discriminatory practices but also at implementing concrete measures to promote an anti-racist justice. Within the scope of its objective, the dissertation contributes to understanding the dynamics between racism, drug policy, and the justice system, providing insights for the formulation of anti-racist public policies and judicial practices.